Integrating IR with CRIS – a novel researcher-centric approach. Issue 3 (5th September 2017) - Rybinski, Henryk; Skonieczny, Lukasz; Koperwas, Jakub; Struk, Waclaw; Stepniak, Jolanta; Kubrak, Weronika
Abstract : Purpose: The purpose of this paper is to present a solution for building an institutional information system (IIS) for the university, so that it combines the functionality of institutional repository (IR) with the functionality of current research information system (CRIS). The paper presents functionality of a system that has been implemented at Warsaw University of Technology (WUT), which solves the requirements of both system types. In addition, applied AI technologies aiming at providing features attractive for the system beneficiaries are presented. Design/methodology/approach: The authors have reviewed various approaches to IIS, analyzed the problems observed by researchers in combining CRIS with IR, and have shown how the problems can be solved within a system that integrates various functionalities. Based on this analysis, the authors have implemented software Ω-Ψ R (OMEGA-PSIR) for an academic IIS, which integrates requirements of both system types, and then deployed it at WUT. Findings: It is shown that although a classical repository is an important part of the CRIS/IR system, the essential value of the solution is in providing analytical tools for "research management." Based on the example of OMEGA-PSIR, the authors have also presented how the researcher-centric approach influences the acceptance rate of the academic community. It is also shown how the researcher-centric approach can take advantage from integrating the conflicting functionalities of IR and CRIS. Practical implications: The paper bridges the gap between theory and practice in the area of IIS for academic institutions. It constructively discusses the role of institutional IR and it provides guides how to develop a system combining functionalities of CRIS and IR, as well as how to make IIS more attractive for the users by making the system researcher centric. Originality/value: The survey of various approaches to IIS is unique. The research-centric approach and its implementation within OMEGA-PSIR system are original. Lessons learned from deploying the software at the WUT are of great value for institutions planning to install IR/CRIS solutions. A survey research concerning the system usability is provided, showing practical usefulness of the proposed approach.